Nurses’ Perspectives on Challenges to Parental Compliance in Childhood Tuberculosis Therapy: A Clinical Study at Prof. Dr. Chairuddin P. Lubis Hospital, University of Sumatra Utara: Strategies for Improving Treatment Adherence - Dewi Elizadiani Suza; Hulwana Husna; Nur Afi Darti; Mahnum Lailan Nasution; Dina Rasmita (Caring: Indonesian Journal of Nursing Science, 2026)
Parental adherence is critical to the successful treatment of pediatric pulmonary tuberculosis (TB) and the prevention of drug resistance. This study explored nurses’ perspectives on barriers to parental adherence in the management of childhood TB. A qualitative phenomenological approach was employed. Semi-structured, in-depth interviews were conducted with 10 nurses who had at least five years of experience in pediatric TB care at Prof. Dr. Chairuddin P. Lubis Hospital, Universitas Sumatera Utara. Participants were recruited through purposive and snowball sampling techniques. Data were analyzed using Colaizzi’s thematic analysis framework. Three major themes emerged: challenges in the clinical management of pediatric TB, barriers to treatment adherence, and nursing interventions to address treatment obstacles. Nurses described emotional burden, fear of infection, complex treatment regimens, workload pressures, limited parental health literacy, socioeconomic difficulties, stigma, and premature discontinuation of treatment when children showed clinical improvement. Effective management of pediatric TB requires family-centered nursing approaches, clear communication, psychosocial support, and multidisciplinary collaboration. Improving nurse-to-patient ratios and strengthening nurses’ communication competencies may enhance parental adherence and contribute to better long-term treatment outcomes. Keyword: Parental Compliance, Pediatric Pulmonary Tuberculosis, Multi-Drug Resistance, Health Education, Tuberculosis